GAMBARAN PERKEMBANGAN PSIKOSOSIAL MAHASISWA KEPERAWATAN DI SURABAYA - Sukma Ayu Candra Kirana; Diyan Mutyah; Nisha Dharmayanti Rinarto (MEDIA ILMU KESEHATAN, 2019)
Background: Young adulthood is a stage of human psychosocial development where individuals begin to accept and assume heavier responsibilities. At this stage of age, intimate relationships begin to be explored and experienced development, this is in line with the reproductive period that starts perfect. Intimacy is how individuals are able to foster intimate / close relationships and love with others. Objective: The purpose of this study is to get a description of the psychosocial development of nursing students in the Surabaya area using an intimacy questionnaire. Methods: The research method used was descriptive analysis by taking a sample of 50 nursing students from 5 nursing institutions in Surabaya so that the total sample was 250. Results: The results in this study that discuss the psychososisal development in young adults obtained the results of most of the psychososisal development is less than optimal with 83 respondents (33.2%) because of the age factor that produces greater than 19 years. Conclusion: So the need for activities that can support psychosocial development in students, especially in supporting the development of intimacy so that the development of intimacy in students can be optimal. Activities that can be carried out such as sharing activities between students and lecturers so that lecturers can help students in fulfilling their development tasks, and students need to play an active role in training themselves to improve the development of intimacy in themselves.